2022
DOI: 10.1016/j.neubiorev.2021.12.013
|View full text |Cite
|
Sign up to set email alerts
|

The Arcuate Fasciculus and language origins: Disentangling existing conceptions that influence evolutionary accounts

Abstract: The Arcuate Fasciculus (AF) is of considerable interdisciplinary interest, because of its major implication in language processing. Theories about language brain evolution are based on anatomical differences in the AF across primates. However, changing methodologies and nomenclatures have resulted in conflicting findings regarding interspecies AF differences: Historical knowledge about the AF originated from human blunt dissections and later from monkey tract-tracing studies. Contemporary tractography studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 109 publications
0
21
0
Order By: Relevance
“…Therefore, a growing number of researchers proposed that language organisation took some of its phylogenetical roots into a gestural system across primate evolution ( Gentilucci and Dalla Volta, 2008 ; Corballis, 2015 ; Tomasello, 2008 ). Consequently, whereas comparative language research has focused on the potential continuities across primate brain circuitry (e.g., Balezeau et al, 2020 ; Becker et al, 2022 ) or vocal and auditory systems (e.g. Boë et al, 2017 ; Jarvis, 2019 ; Wilson et al, 2017 ), the research on gestural communication in apes and monkeys has historically shown a significant interest within this evolutionary framework.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a growing number of researchers proposed that language organisation took some of its phylogenetical roots into a gestural system across primate evolution ( Gentilucci and Dalla Volta, 2008 ; Corballis, 2015 ; Tomasello, 2008 ). Consequently, whereas comparative language research has focused on the potential continuities across primate brain circuitry (e.g., Balezeau et al, 2020 ; Becker et al, 2022 ) or vocal and auditory systems (e.g. Boë et al, 2017 ; Jarvis, 2019 ; Wilson et al, 2017 ), the research on gestural communication in apes and monkeys has historically shown a significant interest within this evolutionary framework.…”
Section: Introductionmentioning
confidence: 99%
“…The left-lateralized perisylvian network, then connects the auditory cortex to Wernicke’s and Broca’s areas through the Arcuate Fasciculus (AF), a bundle of fibers that have been the subject of recent scientific discourses with respect to neuroanatomical differences between the brain of macaque and that of human, within the frontotemporal area. The data favors a “progressive evolution of the AF during primate evolution rather than great leaps that would indicate categorial changes of the AF’s morphology between contemporary species.” [ 37 ] (p. 86). Furthermore, “recent works in human and non-human primates suggest that the AF course and terminations are more similar between species than described before” [ 37 ] (p. 86).…”
Section: Evidence Analysis and Systematic Review Of The Research Lite...mentioning
confidence: 99%
“…The data favors a “progressive evolution of the AF during primate evolution rather than great leaps that would indicate categorial changes of the AF’s morphology between contemporary species.” [ 37 ] (p. 86). Furthermore, “recent works in human and non-human primates suggest that the AF course and terminations are more similar between species than described before” [ 37 ] (p. 86).…”
Section: Evidence Analysis and Systematic Review Of The Research Lite...mentioning
confidence: 99%
See 2 more Smart Citations